2004 EW 95: a phyllosilicate-bearing carbonaceous asteroid in the Kuiper Belt - Seccull, Tom; Fraser, Wesley C.; Puzia, Thomas H.; Brown, Michael E.; Schönebeck, Frederik (The astrophysical journal. Part 2, Letters, 2018)
Models of the Solar System’s dynamical evolution predict the dispersal of primitive planetesimals from their formative regions among the gas-giant planets due to the early phases of planetary migration. Consequently, carbonaceous objects were scattered both into the outer asteroid belt and out to the Kuiper Belt. These models predict that the Kuiper Belt should contain a small fraction of objects with carbonaceous surfaces, though to date, all reported visible reflectance spectra of small Kuiper Belt Objects (KBOs) are linear and featureless. We report the unusual reflectance spectrum of a small KBO, (120216) 2004 EW95, exhibiting a large drop in its near-UV reflectance and a broad shallow optical absorption feature centered at ∼700 nm, which is detected at greater than 4σ significance. These features, confirmed through multiple epochs of spectral photometry and spectroscopy, have respectively been associated with ferric oxides and phyllosilicates. The spectrum bears striking resemblance to those of some C-type asteroids, suggesting that 2004 EW95 may share a common origin with those objects. 2004 EW95 orbits the Sun in a stable mean motion resonance with Neptune, at relatively high eccentricity and inclination, suggesting it may have been emplaced there by some past dynamical instability. These results appear consistent with the aforementioned model predictions and are the first to show a reliably confirmed detection of silicate material on a small KBO.